Development of an Ethnochemistry-Based Learning Module to Strengthen Pancasila Student Profile in the Context of Acid-Base Material - Rika Siti Syaadah; Tiwi Nur Astuti; Andari Thanes Shafitri (PAEDAGOGIA, 2025)
Chemistry is inherently a contextual subject that can be connected to various aspects of everyday life. Indonesia’s rich and diverse cultural heritage offers great potential for integrating chemistry learning with local wisdom through an ethnochemistry. Such integration not only makes learning more meaningful and relevant but also supports the development of the Pancasila Student Profile, which emphasizes values such as creativity, cooperation and appreciation of cultural diversity. However, in practice the integration of ethnochemistry into chemistry learning remains limited. This is reflected in most textbooks, which rarely incorporate. This study aims to develop and evaluate the feasibility of an ethnochemistry-based learning module designed to strengthen the Pancasila Student Profile in the context of acid-base topics. The research method used was Research and Developmnet (R&D) employing the ASSURE model, which consists of the following stages: analyze learners, state objectives, select instructional methods media and materials, utilize media and materials, require learner participations, evaluate and revision. Data were collected instruments, including needs analysis tools such as interview guidelines and questionnaires, as well as student response surveys on the developed module learning. The research subject consisted of 85 eleventh grade students from SMAN 38 Jakarta. Expert validation of the ethnochemistry-based learning module integrated with the Pancasila Students Profile yielded a feasibility score of 94.01%, which falls into the ‘feasible” category. Meanwhile, the implementation with students demonstrated a high level of effectiveness, with an average score of 96.30%. Based on these findings, the developed module is classified as “very good” and is considered highly suitable for use and broad implementation in chemistry learning at the high school level